ANTI-CRISIS PR TECHNOLOGIES IN MAINTAINING THE CORPORATE IMAGE. - Abdullayeva Shahzoda Dilshad kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Today, as time progresses, crisis situations can be observed in any company. In such cases, Anticrisis PR is very important. In particular, any PR manager who knows how to develop an anti-crisis PR strategy and how to use PR technologies can maintain a positive image of his company. In our scientific work, crisis situations in various companies and ways to get out of them using anti-crisis technologies are discussed.